Nickel-catalyzed direct synthesis of N-substituted indoles from amino alcohols and alcohols - Yadav, Vinita; Jagtap, Sayali G.; Balaraman, Ekambaram; Mhaske, Santosh B. (Organic Letters, 2022)
A one-pot cascade approach for the synthesis of N substituted indoles from amino alcohols and alcohols under additive and base-free conditions with the liberation of water as the only stoichiometric byproduct is reported. The commercially available bench-stable Ni(OTf)2 salt in combination with 1,2-bis(dicyclohexylphosphino)ethane (dcype) is very effective for this unprecedented catalytic transformation. A broad range of substrates including aromatic and aliphatic primary alcohols, cyclic and acyclic secondary alcohols, and various substituted 2-aminophenyl ethyl alcohols are employed in the reaction conditions to provide a diverse range of N-alkylated indoles. Mechanistic studies revealed that the reaction proceeds through tandem N-alkylation via hydrogen autotransfer followed by the cyclization of N-alkylated alcohol intermediate.

NHC-catalyzed allylation of aldehydes with MBH carbonates and their michael addition-elimination-cope rearrangement cascade: a route to rac-sacubitril - Kale, Tushar B.; Jagtap, Sayali G.; Mhaske, Santosh B. (Organic Letters, 2025)
We report herein a novel NHC-catalyzed transition-metal-free chemoselective allylation of aldehydes with Morita-Baylis-Hillman (MBH) carbonates using an inorganic base. Fascinatingly, the use of an organic base follows a different mechanism, leading to highly functionalized 1,5-dienes via a Michael addition-elimination reaction followed by [3,3]-sigmatropic Cope rearrangement. The described method harnesses a new Csp2-Csp3 bond to access alpha-methylene-gamma-oxo-gamma-substituted ester derivatives paving a way to facile synthesis of potent natural products and active pharmaceutical ingredients (APIs). A broad range of aromatic and aliphatic aldehydes with MBH carbonates was employed to provide a variety of interesting butanoate and dienyl ketone scaffolds in good to excellent yields. This chemistry has been extended to the efficient syntheses of rac-sacubitril API and gamma-butyrolactone scaffold, which is a privileged core present in many natural products and APIs